2001
DOI: 10.1016/s0022-5347(05)66389-6
|View full text |Cite
|
Sign up to set email alerts
|

Leydig Insulin-Like Hormone, Gubernacular Development and Testicular Descent

Abstract: Insl3 mutants show feminized gubernaculum with deficient mesenchymal core. Insl3 appears to have some role in the gubernacular swelling reaction in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…This showed that Insl3, augmented by either MIS/AMH or dihydrotestosterone, caused similar levels of mitosis as the testis control [19][20][21]. In addition, we were able to show that the fetal gubernaculum contained the putative Insl3 receptor as well as the MIS/AMH type II receptor [22,23].…”
Section: Transabdominal Phasesupporting
confidence: 55%
“…This showed that Insl3, augmented by either MIS/AMH or dihydrotestosterone, caused similar levels of mitosis as the testis control [19][20][21]. In addition, we were able to show that the fetal gubernaculum contained the putative Insl3 receptor as well as the MIS/AMH type II receptor [22,23].…”
Section: Transabdominal Phasesupporting
confidence: 55%
“…Recently, several investigators have suggested that Leydig INSL3 plays an important role in both gubernacular development and transabdominal testicular descent [11,12,19,20]. In addition, INSL3-deficient mutant mice have been reported to exhibit bilateral abdominal UT owing to an impaired development of the gubernaculum [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…No central core of mesenchyme was found in the Insl3 mutants. 4,18 The gubernacular development begins between embryonic day 15.5 to 17.5 and is characterized by rapid proliferation of mesenchymal cells and differentiation of outer layers into myoblasts. 2,19 Insl3 is thought to target the mesenchymal core of the gubernaculum.…”
Section: Discussionmentioning
confidence: 99%